Incidental left paraaortic mass in a patient with gall bladder adenocarcinoma: A diagnostic challenge - Manali Bhatta; Sharma Paudel; Ongden Yonjen Tamang; Prajwal Dahal; Santosh Shrestha; Sabina Parajuli (Radiology Case Reports)
Incidental adrenal masses are frequently detected due to the extensive use of cross-sectional imaging, with about 3% to 7% of adults estimated to have them. Paragangliomas and pheochromocytomas (PPGL), rare tumors originating from paraganglia tissues, including the adrenal medulla, continue to be imaging mimics, necessitating a multimodal approach for accurate diagnosis. We report a case of 72-years male presenting with intermittent pain abdomen for the past 1 year. Preliminary imaging by ultrasound revealed a suspicious gall bladder polypoidal lesion along with choledochal cyst for which further characterization was done with both CT and MRI. On imaging besides defining the findings seen in USG, we encountered a large heterogeneously enhancing possible left adrenal incidentaloma. A homogeneously hyper enhancing lesion along the paraganglia distribution, with no evidence of washout and a high T2 signal, is a hallmark imaging characteristic of pheochromocytomas and paragangliomas. However, around 35% of atypical lesions, often altered by degenerative changes, deviate from these typical imaging patterns, presenting a diagnostic dilemma. Histopathological analysis, including immunohistochemistry, biochemical testing, and functional imaging, can offer valuable insights to help diagnose and aid in predicting prognosis.